PERAN GURU PPKn TERHADAP PEMBENTUKAN PERILAKU PESERTA DIDIK SESUAI NILAI-NILAI PANCASILA DI SMA NEGERI 1 AMANDRAYA TAHUN PEMBELAJARAN 2020/2021 - Mesrawati Putri Ndruru; Eka Periaman Zai; Sesuaikan Sarumaha (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2020)
This research is motivated by the behavior of students who are not in accordance with the values of Pancasila at SMA Negeri 1 Amandraya. To address this, the researchers conducted research on the role of Civics teachers in shaping student behavior according to Pancasila values at SMA Negeri 1 Amandraya. This study aims (1) to identify and describe the role of Civics teachers in shaping student behavior according to Pancasila values at SMA Negeri 1 Amandraya; (2) To find out and describe the formation of student behavior according to the values of Pancasila at SMA Negeri 1 Amandraya. The approach used in this research is descriptive method and the type of qualitative research. Data collection techniques are carried out by (1) Observation; (2) Interview;and (3) Documentation study. Analysis of the data used (1) data reductio; (2) data presentation; and (3) conclusion drawing. The results of the research on the role of civic education teachers on the formation of student behavior according to Pancasila values at SMA Negeri 1 Amandraya, namely the role of the teacher as a teacher, mentor, role, model, and motivator has been carried out well and formation of student behavior according to the values of Pancasila, namely by doing good habits and giving examples to students researchers suggest that teacher should play a role in shaping student behavior in accordance with values of Pancasila continue to be improved and taught, so that students become a generation of intelligent and moral people.